Introduction to family counseling : a case study approach - Esposito, Judy; Hattem, Abbi (Los Angeles : SAGE, 2017)
The book is organized into three parts: An overview on families An overview of frequently used models of family therapy at the undergraduate level Presentation of ethics, trends, and services in counseling families Engaging transcripts of family counseling sessions bring concepts and theories to life while showing assessment tools, theories, needs for additional services, and ethical issues Case study approach allows students to follow how family counselors think and lets them examine family issues such as substance abuse, domestic violence, and co-parenting in blended families'Stop-and-Think' features challenge students to expand their perspective from individuals to families and helps students learn to think about the family in terms of group dynamics Discussion topics and exercises aimed at using the students' own experiences with families as ...
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: Family psychotherapy; Family counseling